Experimental research on damage identification of topping dangerous rock structural surface based on dynamic characteristic parameters - Jia, Yanchang; Jiang, Tong; Yin, Yanli; Yu, Guo; Wang, Lijin (Frontiers in Earth Science, 2022)
Rock block tilting is one of the most common types of dangerous rock block failures with no clear indicator of displacement prior to failure. Existing stability evaluation methods remain limited in their ability to constrain the non-penetrating section area, which is closely related to rock stability, and stability evaluations are therefore associated with large uncertainties. The dynamic characteristic parameters of toppling dangerous rock are closely related to structural plane strength. Under vibration loading, rainfall, and/or excavation unloading conditions, the structural plane becomes damaged and the dynamic characteristic parameters change. In this study, we present a dynamic characteristic model of rock tilting and identify the quantitative and qualitative relationship between dynamic characteristic parameters and the bonded area of the structural plane. The model accuracy is verified by experiments. The experimental results show that the damping ratio decreases linearly with structural plane damage, whereas the maximum vibration speed and particle trajectory increases nonlinearly and the natural vibration frequency decreases nonlinearly. The dynamic characteristic model and experimental results can be used to evaluate the degree of structural surface damage of toppling dangerous rock.